Potensi Isoflavon Genistein Sebagai Terapi Suportif Imunonutrisi Pada Pasien Kanker Payudara - Regina Triswara; Ahmad Farishal; Bintang Abadi Siregar (Medula, 2020)
Breast cancer is a malignancy in breast cells that grow out of control with a variety of mechanisms and risk factors. Breast cancer can be started from the ducts or lobular breasts. Breast cancer has a high incidence and high mortality in the Asian region due to various things, especially the process of early detection and therapy. Prevention stage is preferred over surgical or chemotherapy therapy. The condition of breast cancer patients must have a strong and tough immune system to supply cancer cells so that the need for proper nutrition is very much needed. Soybeans are rich in isoflavones known as antioxidants, antibacterial and most recently have anticancer potential. Genistein isoflavones in soybeans will be more active after the fermentation process and show the potential of cancer cell inhibitors by changing the phase of carcinogenesis with hormone receptor pathways and Nf-Kb-Akt signaling. Genistein is also proven as an inhibitor of angiogenesis in cancer cells. Further clinical trials need to be carried out on safety and the right dosage to be applied as immunonutrition in breast cancer patients.